(untitled) (Research, Society and Development, 2020)
The central theme of the article is the different learning participative methodologies, based on Bloom Revised Taxonomy, applied in many courses at the UNIFACIG University Center. The justification for the use of Taxonomy theoretical support focuses on the point of reflective, critical and creative development of students. The objective of the study is to present a systematic revision of papers published concerning to active methodologies developed at UNIFACIG, seeking out to verify the contribution of thematic development of a critical, reflective and collaborative professional and the ability to apply the learned content and also the state of the art in which the theme is applied as a didactic strategy in different courses. As a methodological design, it was opted a systematic review of studies published in different Forums conducted by Sthem-Brasil Consortium totaling 21 works. In view of analyses carried out in the various works of the institution, it is clear that application of active methodologies in teaching and learning process are preponderant aspects of a better content development. Whether using simulated practices or real experiences; communication, interaction between participants, restlessness and involvement are intrinsic parts of the process, which leads to more meaningful and lasting learning. It is noticed that the desired result was achieved, because, in general, studies show extremely positive results: a more critical, reflective and instigating university education, with more collaborative and creative students and, specially, with social and responsible conscience.